1999
DOI: 10.1007/bf02234222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of restorative proctocolectomy on renal and adrenal function

Abstract: These results show that restorative proctocolectomy with ileal pouch-anal anastomosis and protective loop ileostomy significantly influences fluid, electrolyte, and acid-base balance. Functional secondary hyperaldosteronism is of central importance for subsequent renal recompensation. Approximately one-half year after ileostomy closure, the endogenous hormones with mineralocorticoid effects returned to normal levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 21 publications
1
10
1
Order By: Relevance
“…These results suggest that the patients after the second operation for UC were dehydrated even after 20-30 weeks had passed since the first operation in which the ileostomy was constructed. This result coincided with that in a previous study by Huber et al that reported increased plasma levels of aldosterone in patients after total colectomy 8) . Delin et al reported the shorter length of small bowel after proctocolectomy with various ileal resections, the more the increase in plasma levels of renin and aldosterone after the operation, and they concluded that measurement of renin and aldosterone levels should be used for evaluation of the severity of sodium deficiency 9) .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results suggest that the patients after the second operation for UC were dehydrated even after 20-30 weeks had passed since the first operation in which the ileostomy was constructed. This result coincided with that in a previous study by Huber et al that reported increased plasma levels of aldosterone in patients after total colectomy 8) . Delin et al reported the shorter length of small bowel after proctocolectomy with various ileal resections, the more the increase in plasma levels of renin and aldosterone after the operation, and they concluded that measurement of renin and aldosterone levels should be used for evaluation of the severity of sodium deficiency 9) .…”
Section: Discussionsupporting
confidence: 93%
“…The patients were assigned randomly into two groups using a table of random numbers. The patients in group A initially ingested ORS (Na + 50 mEq/L, K + 20 mEq/L, Cl 50 mEq/L, Mg 2+ 2 mEq/L, P 2 mmol/L, Lactate 31 mEq/L, Glucose 1.8%) (1000 mL/day) for the first 7 days (days 1-7) and mineral water (Na + 0.49 mEq/L, K + 0.046 mEq/L, Mg2+ 0.44 mEq/L, Glucose 0%) (1000 mL/day) was given for the next 7 days (days [8][9][10][11][12][13][14]. Conversely, patients in group B initially drank mineral water (1000 mL/day) for the first 7 days and ORS (1000 mL/day) was given for the next 7 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with an ileostomy are particularly vulnerable to these problems because of the metabolic acidosis of bicarbonate wasting, but also because of the reduced total body fluids, resulting in stimulation of the renin-angiotensin mechanism, intrarenal vasoconstriction, and secondary hyperaldosteronism [14,15]. The sodium bicarbonate therapy in our patient was probably of additional benefit by correcting these abnormalities as well as the acidosis.…”
Section: Discussionmentioning
confidence: 84%
“…In humans, Huber et al thoroughly investigated the renal and adrenal function in the process of an elective two-step proctocolectomy with ileal pouch-anal anastomosis by measuring the electrolyte and hormone metabolite levels in both the urine and blood. 25 They also concluded that functional secondary hyperaldosteronism plays a central role in subsequent renal adaptation. The present data support the idea that renal adaptation following a total proctocolectomy depends, at least in part, on the molecular induction principally regulated by circulating aldosterone.…”
mentioning
confidence: 98%